KOMUNIKASI POLITIK PEREMPUAN DI KEDIRI - Citra Orwela (Pusat Studi Gender dan Anak, 2023)
The limited number of women involved in political activities, both local and national, is an exciting problem to be examined. Until now, research on women politicians and leadership has not been explored. Starting from these problems, the author wants to go deep into deep research on